Unravelling the Potential Cytotoxic Effects of Metal Oxide Nanoparticles and Metal(Loid) Mixtures on A549 Human Cell Line - Rosário, F (2020)
Humans are typically exposed to environmental contaminants’ mixtures that result in different toxicity than exposure to the individual counterparts. Yet, the toxicology of chemical mixtures has been overlooked. This work aims at assessing and comparing viability and cell cycle of A549 cells after exposure to single and binary mixtures of: titanium dioxide nanoparticles (TiO2NP) 0.75–75 mg/L; cerium oxide nanoparticles (CeO2NP) 0.75–10 μg/L; arsenic (As) 0.75–2.5 mg/L; and mercury (Hg) 5–100 mg/L. Viability was assessed through water-soluble tetrazolium (WST-1) and thiazolyl blue tetrazolium bromide (MTT) (24 h exposure) and clonogenic (seven-day exposure) assays. Cell cycle alterations were explored by flow cytometry. Viability was affected in a dose- and time-dependent manner. Prolonged exposure caused inhibition of cell proliferation even at low concentrations. Cell-cycle progression was affected by TiO2NP 75 mg/L, and As 0.75 and 2.5 μg/L, increasing the cell proportion at G0/G1 phase. Combined exposure of TiO2NP or CeO2NP mitigated As adverse effects, increasing the cell surviving factor, but cell cycle alterations were still observed. Only CeO2NP co-exposure reduced Hg toxicity, translated in a decrease of cells in Sub-G1. Toxicity was diminished for both NPs co-exposure compared to its toxicity alone, but a marked toxicity for the highest concentrations was observed for longer exposures. These findings prove that joint toxicity of contaminants must not be disregarded.